The integration of blockchain technology and internet of things in realising sustainable agro food supply chains - Moyo, Judith (Logistics, supply chain, sustainability and global challenges, 2025)
The world population is projected to reach 9 billion by 2050, which is 34% higher than it is now and the demand for agricultural food is expected to increase as well. Research has shown that the demand for soya beans is on the increase owing to its contribution in cooking oil, stock feed and other by-products. On average, Zimbabwe’s soya bean national output production is only enough to meet 30% of national demand, which is supplemented by imports from South Africa, Zambia and Malawi. Constraints in information gathering, storage, safeguarding, and sharing, environmental changes and escalations in input prices has become a catch phrase for soya bean supply systems failure. This study’s objective is to explore strategies which can be adopted by soya bean small to medium scale farmers to realise sustainability in their supply chains and build food security in Mashonaland Central Province of Zimbabwe. This study therefore proposes the integration of Blockchain Technology (hereafter: BCT) and Internet of Things (hereafter: IoT) to improve sustainability in the soya bean supply chain systems in Zimbabwe. The researchers adopted a pragmatism research philosophy premised on the mixed methods research approach because quantitative data alone is not sufficient to answer the research questions. Quantitative data were analysed using STATA 15 and NVivo version 16 was used to analyse qualitative data. Using Krejcie and Morgan (1970) a sample size of 375 farmers was randomly selected to respond to questionnaires. Six (6) AGRITEX officers and two (2) Agronomists were purposefully selected from the six (6) districts of Mashonaland Central Province and were interviewed. Findings from the research showed that there is minimal uptake of Artificial Intelligence (hereafter: AI) technologies in soya bean supply chains in Mashonaland Central Province which has slowed the improvements in production and sustainability of agro-supply chains. The study recommends the integration of blockchain and IoT technologies to improve sustainability in soya bean production in Zimbabwe.
Keywords: agro food; block chain technologies; dobavna veriga; IoT technologies; kmetijsko-živilski sektor; supply chain; tehnologije IoT; tehnologije verižnih blokov